2012
DOI: 10.1007/s00449-012-0841-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of silver nanoparticles using Cynodon dactylon leaves and assessment of their antibacterial activity

Abstract: Many methods of synthesizing silver nanoparticles (Ag-NPs) by reducing Ag⁺ ions using aqueous/organic extracts of various plants have been reported in the past, but the methods are rather slow. In this investigation, silver nanoparticles were quickly synthesized from aqueous silver nitrate through a simple method using leaf extract of a plant--Cynodon dactylon which served as reducing agent, while sunlight acted as a catalyst. The formation of Ag-NPs was indicated by gradual change in colour and pH and confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 28 publications
1
35
0
1
Order By: Relevance
“…3 ml of Plant extract was added to 60 ml of 10 -3 M AgNO 3 solution and the reaction was left to take place at ambient conditions [12]. The observed change in color from colorless to transparent yellow and finally to a dark brown with time indicates the formation of AgNPs.…”
Section: Synthesis Of Silver Nanoparticlesmentioning
confidence: 99%
“…3 ml of Plant extract was added to 60 ml of 10 -3 M AgNO 3 solution and the reaction was left to take place at ambient conditions [12]. The observed change in color from colorless to transparent yellow and finally to a dark brown with time indicates the formation of AgNPs.…”
Section: Synthesis Of Silver Nanoparticlesmentioning
confidence: 99%
“…The observed absorbance peak at 420 nm (Fig. 1) is due to the surface plasmon resonance [16,21] and the appearance of peak shows the reduction of Ag + to silver nanoparticles hence it can be concluded that Carissa carandas leaf extract behaves as a reducing agent. The UV-visible analysis also showed that these nanoparticles were found to be stable even after six months.…”
Section: Uv-visiblementioning
confidence: 92%
“…Then the sample was kept into the incubator for 3 h in dark place, the colour changed from yellow to brown. It indicates synthesis of silver nanoparticles [20,21]. The solution after change of colour was used for further characterization of silver nanoparticles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It also contains mineral constituents, crude proteins and chemical constituents like linolenic acid, hydro quinine, and hexadecanoic acid. It also shows the DNA protective activity [14,15]. In our research report, the small sized titanium dioxide nanoparticles was obtained, using of the Cynodon dactylon leaf extract and it is found to show a good antibacterial and anticancer activity against E. Coli and A549cell lines.…”
Section: Introductionmentioning
confidence: 94%